Penerapan Pogram P5-PPRA Dengan Tema Hidup Berkelanjutan dalam Mendidik dan Membentuk Karakter Siswa Kelas I MI Plus Ja-Alhaq - Fitriani, Maria Desi; Andreani, Mesi; Khoridah, Navisatul; Maharani, Selly Resti (PPSDP Undergraduate Journal of Educational Sciences, 2024)
This research aims to describe how character education is implemented through P5-PPRRA at MI Plus Ja-alhaq Bengkulu City. The research method used is qualitative research. Test the validity of the data using source triangulation. Namely Interviews, Observations, and documentation. Researchers conducted interviews with the Principal, Deputy Principal for Curriculum, Class I Teachers, and several Class I students. This research found that the P5-PPRRA MI Plus Ja-alHaq activities had only been implemented in classes I and IV. The project carried out by class I raised the theme of sustainable living. This theme is based on the student's problem, namely that he doesn't like eating vegetables. Therefore, this project was realized through planting and caring for vegetables. It was found that students were very enthusiastic in carrying out activities of planting and caring for these vegetables. They are together and help each other in taking care of the vegetables. The existence of the P5-PPRA activity is useful for students because students can have the opportunity to learn, such as learning to work together or work together in implementing projects. Through this activity, students can form and strengthen the character of the Pancasila Student Profile, namely working together. Apart from that, it is also to form the character of faith, devotion to God Almighty, and noble character through habits such as caring for and watering plants as a creation of Allah SWT. This activity has an excellent impact on students' character education so that students can implement the characters formed from this project in their daily lives. It can also have a good impact on increasing students' awareness of protecting the surrounding environment.